The caspase inhibitor zVAD increases lung inflammation in pneumovirus infection in mice - van den Berg, Elske (Physiol Rep, 2015)
Severe respiratory syncytial virus (RSV) disease is a frequent cause of acute respiratory distress syndrome (ARDS) in young children, and is associated with marked lung epithelial injury and neutrophilic inflammation. Experimental studies on ARDS have shown that inhibition of apoptosis in the lungs reduces lung epithelial injury. However, the blockade of apoptosis in the lungs may also have deleterious effects by hampering viral clearance, and importantly, by enhancing or prolonging local proinflammatory responses. The aim of this study was to determine the effect of the broad caspase inhibitor Z-VAD(OMe)-FMK (zVAD) on inflammation and lung injury in a mouse pneumovirus model for severe RSV disease. Eight- to 11-week-old female C57BL/6OlaHsd mice were inoculated with the rodent-specific pneumovirus pneumonia virus of mice (PVM) strain J3666 and received multiple injections of zVAD or vehicle (control) during the course of disease, after which they were studied for markers of apoptosis, inflammation, and lung injury on day 7 after infection. PVM-infected mice that received zVAD had a strong increase in neutrophil numbers in the lungs, which was associated with decreased neutrophil apoptosis. Furthermore, zVAD treatment led to higher concentrations of several proinflammatory cytokines in the lungs and more weight loss in PVM-infected mice. In contrast, zVAD did not reduce apoptosis of lung epithelial cells and did not affect the degree of lung injury, permeability, and viral titers in PVM disease. We conclude that zVAD has an adverse effect in severe pneumovirus disease in mice by enhancing the lung proinflammatory response.